Fingerprint Based Authentication Architecture for Accessing Multiple Cloud Computing Services using Single User Credential in IOT Environments. (January 2021) - Alemu, Biniyam; Kumar, Rajesh; Sinwar, Deepak; Raghuwanshi, Ghanshyam
Abstract: Cloud computing technology provides access to the pool of configurable resources including storage space, application, services and on demand network. Involvement of Cloud with the organization minimizes organization efforts toward fulfilling its customer's needs. One of the major advantages of cloud computing is the Single Sign On (SSO) technique that allows the user to access multiple application services using a single user credential. In cloud computing, there are many issues, and challenges to be discussed. However, prevention from security attacks is much more difficult in preserving privacy of user agents. This paper has proposed SSO-based bio-metric authentication architecture for cloud computing services to overcome the security and privacy attacks. Bio-metric authentication is effective for resources controlled by end devices at the time of accessing the cloud services since these devices are computationally inefficient for user information processing during authentication. Accordingly, security attack in the cloud computing gets minimized using the proposed architecture. The proposed architecture also includes a novel approach in which there exist one to one relationship between user agent and the service provider. In this user agents can use their fingerprint while requesting for registration and accessing different cloud application services at cloud. Based on comparative study with several existing architectures, the highlights of the proposed architecture have been presented.